2020
DOI: 10.4258/hir.2020.26.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning and Initial Nursing Assessment-Based Triage System for Emergency Department

Abstract: An emergency department (ED) is a complex scene where various diseases and processes are intertwined. Annually, over 4.8 million patients visit EDs in Korea, and 137.8 million visit EDs in the United States [1,2]. Moreover, the number of patients and the severity of their complaints are increasing due to aging of the population and advances in emergency medicine [3]. When resources are not sufficient, the increased load on EDs results in a poor quality of care, which leads to a suboptimal outcome [4]. Triage s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Through an emergency department triage system based on machine learning and the initial nursing assessment, an efficient system to predict adverse clinical outcomes could be created. This new system was more efficient than the previous traditional system [12].…”
Section: Objectivesmentioning
confidence: 82%
“…Through an emergency department triage system based on machine learning and the initial nursing assessment, an efficient system to predict adverse clinical outcomes could be created. This new system was more efficient than the previous traditional system [12].…”
Section: Objectivesmentioning
confidence: 82%
“…A recent multinational study found that the National Early Warning Score (NEWS) can predict mortality among adult medical patients in the ED with an AUROC of 0.73, and the combination of the NEWS and laboratory biomarkers yielded an AUROC of 0.82 [ 16 ]. Some investigators developed machine-learning models for the prediction of death or admission to intensive care units among ED patients and reported the AUROCs of their models to be between 0.84 and 0.87 [ 15 , 28 ]. The AUROC of the scoring system for survival prediction among general ED patients developed in this study was 0.883, which can be regarded as adequate, considering the fact that patients with diverse complaints were included, no laboratory data are required, and the calculation is much simpler than the calculations needed for trauma scores based on anatomical injuries or sophisticated machine-learning-based models.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high rate of exclusion because of missing values may have caused selection bias; more cases were likely included from centers with relatively high proportions of patients with severe cases, which were also likely to have policies in place regarding the recording of vital signs and detailed medical records. Although some existing scoring systems have been derived from populations with fewer missing values, they tend to have been derived from the data obtained in a single hospital, including the Rapid Emergency Medicine Score (REMS) and ViEWS, which later served as a template for NEWS [ 15 , 29 – 31 ]. Our results are more reliable than the results in those studies because our data were derived from EDs at various levels and of different sizes; however, the amount of missing data was a limitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the internal test data set, consisting of 1691 images (1075 malignant and 616 benign), and federated learning-trained deep learning algorithms, the accuracies of VGG19, SE-ResNet50, ResNet50, SE-ResNext50, and ResNext50 were 79.5%, 77.9%, 77.4%, 77.2%, and 73.9%, respectively (Table 2; Table S1 in Multimedia Appendix 1). Figure 3 shows the receiver operating characteristic curve [15] of each network for the internal test data set. Area under the receiver operating characteristic (AUROC) curve values of SE-ResNext50, ResNext50, VGG19, SE-ResNet50, and ResNet50 were 87.6%, 86.0%, 82.0%, 79.9%, and 78.9%, respectively.…”
Section: Federated Learning Performancementioning
confidence: 99%